Implementation of Test Item Analysis for Learning Evaluation at SMAS YKPP Dumai - Widodo, Pulla Pandika (P3M Politeknik Negeri Bengkalis, 2024)
The activity of analyzing items is an activity that must be carried out by the teacher, this is done to evaluate the quality of the test questions used during the exam. So far, teachers have used the anbuso excel application to complete the analysis. The existing application requires entering student answer data and question answer keys one by one, this allows data errors when entering student answer data, and can be imagined if the teacher teaches more than one class it will take more time to be able to complete the analysis and increase the teacher's workload. This research aims to create a question analysis application with the codeigneter framework to help teachers get question analysis results quickly and efficiently without the need to enter student answers one by one. The application created presents analysis data based on the level of difficulty, differentiating power and function of the examiner which is made in tabular form so that it is easy to read. The application provides several users such as teachers, students and admins with different menu access rights. This application allows teachers to enter or change questions along with the answer key, view answer results and get question analysis. Students can get the results of the exam answers available after the exam. For admins, it helps in managing user data, monitoring exam students and activating exams. From the results of the analysis produced by the application, the teacher can use the question criteria.